ECHOES OF THE INFORMATION AGE: A CONTENT ANALYSIS OF U.S. NEWSPAPERS DURING THE RISE OF INTERNET 1.0 - Jensen, Sarah Elizabeth; Steinberg, Michael Aaron (Ayden Journal of Management and Social Sciences, 2024)
This content analysis investigates the characteristics of Internet news in the year 2001, marking a pivotal moment when much of the U.S. press transitioned to online platforms. Building upon previous research on print news, this study examines the fundamental elements of news stories, including the "who, what, when, where, why, and how." The findings reveal a continuation of established trends, with notable shifts towards longer stories and increased explanations of causality and methodology. Moreover, a notable emphasis on groups over individuals, particularly officials and external sources, is observed. These changes suggest that the migration to Web 1.0 further solidified the professional authority of journalists. However, an intriguing transformation is also discernible as news outlets redirected their focus toward local markets and fostering connections between events. This evolution is characterized by an upsurge in the inclusion of events within news stories, and their contextualization within historical narratives. Furthermore, the geographical locations of news stories began to gravitate closer to the arenas where individuals engage as active citizens, a noteworthy reversal of a century-long trend.